Fat embolism syndrome in a patient that sustained a femoral neck fracture: A case report - Otter, L. A. S. den; Vermin, B.; Goeijenbier, M. (Frontiers in Medicine, 2022)
Abstract Background: We present a case of a patient with a femoral neck fracture that shows neurological impairment and respiratory distress one day after trauma, caused by the Fat Embolism Syndrome with the presence of Cerebral Fat Embolisms. Case summary: A 75 year old female remained unresponsive after a hemi arthroplasty was performed because of a one day old femoral neck fracture. She rapidly developed respiratory insufficiency and an obstructive shock with right ventricle dilatation on transthoracic echocardiography. The diffusion-weighted MRI brain images showed the ‘Starfield’ pattern, a radiologic phenomenon typical for FES. During three weeks of ICU admission the neurologic state slowly ameliorated. Conclusion: The rare FES is a clinical diagnosis with mainly respiratory, neurologic and dermatologic symptoms in the setting of a trauma patient. Fat embolisms are able to reach the brain without the presence of a patent foramen ovale to cause neurological symptoms. Diagnosing FES remains challenging but the distinctive ‘Starfield’ pattern on MRI scans is promising.